Too many cooks in the kitchen: HPV driven carcinogenesis – The result of collaboration or competition? - Weimer Kathleen (Tumour Virus Research)
Infection by Human Papillomaviruses accounts for the most widespread sexually transmitted infection worldwide. Clinical presentation of these infections can range from subclinical and asymptomatic to anogenital cancers, with the latter associated with persistent infection over a significant period of time. Of the over 200 isotypes of the human virus identified, a subset of these has been characterized as high-risk due to their ability to induce oncogenesis. At the core of Papillomavirus pathogenesis sits three virally encoded oncoproteins: E5, E6, and E7. In this review we will discuss the respective roles of these proteins and how they contribute to carcinogenesis, evaluating key distinguishing features that separate them from their low-risk counterparts. Furthermore, we will consider the complex relationship between this trio and how their interwoven functional networks underpin the development of cancer.